Student Management Strategy in the Integration of Aqidah Akhlak to Strengthen Islamic Character at MI Tarbiyatul Athfal: Strategi Manajemen Siswa dalam Integrasi Aqidah Akhlak untuk Penguatan Karakter Islami di MI Tarbiyatul Athfal - Halimatus Sa'diyyah; Sukarman; Kholilur Rohman; Frans Angger Bagus Sancoko; Abdulasi Kalupae (Mapendis: Jurnal Manajemen Pendidikan Islam, 2024)
Character building for students from an early age is an important aspect of Islamic education, and the subject of Aqidah Akhlak in Madrasah Ibtidaiyah (MI) plays a central role in the internalization of Islamic values. This study aims to analyze student management strategies in integrating Aqidah Akhlak to strengthen Islamic character at MI Tarbiyatul Athfal. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation of teachers, the madrasah principal, and students in grades IV-VI. The findings indicate that the learning strategies implemented include the use of exemplary stories, daily habits, and integration in worship and extracurricular activities. Manifestations of student character such as honesty, responsibility, and politeness show significant improvement, although internalization of values ​​is still at the stage of external compliance. Supporting factors include teacher commitment, a visionary madrasah principal, and parental participation, while the main obstacles are the high teaching load, lack of facilities, and the absence of affective assessment standards. The conclusion of this study is that the holistic integration of Aqidah Akhlak can strengthen the formation of Islamic character, but requires systemic support from madrasah and government policies for optimal achievement.